Chapter 6. Maize improvement for drought-limited environments - Edmeades, Gregory O.; Bänziger, Marianne; Ribaut, Jean-Marcel (CRP Press, 2024)
It is generally agreed that the two largest causes of maize yield loss in the tropics and subtropics are drought and inadequate fertility, and, for this reason, breeding for tolerance to these stresses has become a major focus of CIMMYT's Maize Program. There is also evidence (E. Knapp, unpublished data; Reeder, 1997) that maize yields in major temperate production areas, such as the central Corn Belt of the United States, even though they have risen substantially in the past fifty years, have shown much greater fluctuations from year to year in the last thirty years. This is attributed mainly to seasonal variation in rainfall, since soil fertility levels have been rising and weed control is generally excellent. Losses to drought alone in the tropics may total 24 million tonnes (t) per year, or around 17 percent of well-watered production (Edmeades, Bolaños, and Lafitte, 1992), but have been as high as 60 percent in severely affected regions such as southern Africa in 1991 to 1992. Severe losses such as these can be expected to lead to a close association between seasonal rainfall and national or regional average maize yields, and this has been observed in eastern and southern Africa (Edmeades, Bänziger, Chapman, Ribaut, and Bolaños, 1997). This suggests that drought is a pervasive cause of yield instability in maize-based cropping systems in most years and environments. Within a particular field, localized yield losses can reach 100 percent where rainfall falls below 350 to 500 millimeters (mm) in the crop season, or where there are patches of soil that are sandy or shallow, provided the period of severe water deficit coincides with flowering. Eyherabide and colleagues (1997), in a simulation study of major maize-producing areas of Argentina, noted that in the region where yields are the highest, there is a 50 percent probability of at least a 50 mm deficit in water during the flowering period. They concluded that the average annual yield loss caused by drought in Argentina equaled 1.2 million tons of grain, or about 15 percent of annual production.